Framing the black body - J. Butler (Law Text Culture, 1998)
Black Letter Law - the basic principles of law embodied in the statutes and in the court records of a particular jurisdiction. Black Letter Law - a display of the works of three artists held at the Law School of the University of Sydney from October 22 to November 11, 1997.